Sociological Factors Of Imam Syafi’is Qaul Qadim And Qaul Jadid - Nawirman; Kurniati; Misbahuddin; Nurchamidah (al-Afkar, Journal For Islamic Studies, 2023)
Imam Syafi'i's ideas regarding qaul qadim and qaul jadid are interesting to observe. From the idea that shows flexibility in the application of Islamic sharia, Islamic law, or Islamic fiqh, it appears that Imam Syafi'i has provided a methodical framework in addressing the application of Islamic sharia, Islamic law, or Islamic fiqh which has relevance to various social contexts that covers it. This implies that Islamic sharia, Islamic law, or Islamic law is a process of grounding theocentric values ​​that are ideal and sacred to anthropocentric values ​​that are very dynamic and profane. In this process, Imam Syafi'i's constructive and innovative ideas regarding qaul qadim and qaul jadid, along with various sociological factors that became the background for changing his views, had practical implications for the birth of a methodical framework for the application of Islamic sharia, Islamic law, or Islamic fiqh that can be applied in different contexts of place, time or circumstances